Journal of Halal product and research - Universitas Airlangga. Pusat Riset dan Pangembangan Produk Halal; Universitas Airlangga. Pusat Halal; Universitas Airlangga. Lembaga Ilmu Hayati, Teknik, dan Rekayasa; Higher institute: https://lihtr.unair.ac.id (Universitas Airlangga, 2018)
Dedicated to improving the insight about research and development of halal products, also to be used as references for academics, practitioners, policy-makers, and the general public.
Keywords: Halal food : Periodicals; Muslims : Dietary laws : Periodicals; Islamic cooking : Periodicals; Halal food industry : Indonesia : Periodicals